Recitation-Based Teaching Material Development for Cation Qualitative Analysis Learning - Abudarin Abudarin; I Made Sadiana; Sri Wahyutami; Syarpin Syarpin; Chuchita Chuchita; Nurjennah Nurjennah (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2021)
This study aims to develop recitation-based teaching materials for learning qualitative analysis of cations. The procedure for developing teaching materials adopts the 4-D development model (Define, Design, Develop, Dissemination) from Thiagarajan. The development results were tested theoretically and empirically. The theoretical feasibility test was carried out using expert judgment, including chemist expert, pedagogic expert, and learning media. Empirical feasibility was tested through legibility tests and limited implementation tests. Based on the expert assessment, the recitation method based teaching materials developed in this study is content valid with individual readability of 87,86% and group readability of 89,32%. The results of testing the implementation of teaching materials in the learning process showed that recitation-based teaching materials were effective, in guiding students to do independent learning activities with an effectiveness of 84,16%. The use of Cation Qualitative Analysis teaching materials based on the recitation method in online learning is effective in increasing student understanding of qualitative analysis of cations with an N-gain value of 0,81. The students' ability to complete study assignments with the help of worksheets on teaching materials has a positive correlation, with an increase in concept understanding (r = 0,91) with a contribution value of 88,43%.